Comprehensive care to women with tuberculosis in the family health strategy - de Sá, Lenilde Duarte; do Nascimento Santos, Ana Rita Bizerra; Oliveira, Annelissa Andrade Virgínio de; Andrade, Séfora Luana Evangelista de; Nogueira, Jordana de Almeida; Rodrigues, Débora César de Souza (Revista de Enfermagem UFPE on line, 2011)
ABSTRACT Objective: to analyze the actions developed by the family health team in the care to the woman with tuberculosis in a priority town of Paraiba, Brazil, under the perspective of comprehensiveness. Methods: this is a research with a qualitative design, carried out in a town from the metropolitan region of Joao Pessoa, Paraiba, Brazil, considered a priority one for controling the disease in the state of Paraiba. A semi-structured interview was used with 8 professionals from 4 teams of the Family Health Strategy who were following up women with tuberculosis during the period of information collection. For analyzing the empirical material the content analysis technique was used, in its thematic modality. Results: the results found highlight the problem of tuberculosis in the town concerned, where the health professionals recognize the social precariousness in which the women with tuberculosis live, demonstrate to have a close look to the context in which these women live, and develop actions under the perspective of comprehensiveness and intersectoriality. Conclusion: the issue of gender permeates care, revealing that the professionals work under the perspective of increasing the care provision. In the interaction with the female users a bond is established. Actions promoting empowerment are not observed. Instead of them, attitudes expressing generosity are observed. Descriptors: tuberculosis; family health; women’s health. RESUMO Objetivo: analisar as ações desenvolvidas pela equipe de saúde da família no cuidado à mulher com tuberculose em um município prioritário da Paraíba, sob a perspectiva da integralidade. Método: trata-se de pesquisa do tipo qualitativa, realizada em um município da região metropolitana de João Pessoa-PB, considerado prioritário para o controle da doença no estado da Paraíba. Utilizou-se a entrevista semiestruturada com 8 profissionais de 4 equipes da Estratégia Saúde da Família que estavam acompanhando mulheres com tuberculose no período da coleta de informações. Para a análise do material empírico utilizou-se a técnica de análise de conteúdo, em sua modalidade temática. Resultados: os resultados encontrados realçam o problema da tuberculose no município em questão, onde os profissionais de saúde reconhecem a precariedade social em que vivem as mulheres com tuberculose, demonstram possuir um olhar próximo ao contexto em que vivem essas mulheres, e desenvolvem ações sob a perspectiva da integralidade e intersetorialidade. Conclusão: a questão de gênero perpassa o cuidado, revelando que os profissionais atuam sob a perspectiva da ampliação do cuidado. Na interação com as usuárias forma-se um vínculo. Não se observam ações que promovam empowerment. Em vez delas são observadas atitudes que expressam generosidade. Descritores: tuberculose; saúde da família; saúde da mulher. RESUMEN Objetivo: analizar las acciones desarrolladas por el equipo de salud de la familia en la atención a la mujer con tuberculosis en un municipio prioritario de Paraiba, Brasil, bajo la perspectiva de la integralidad. Métodos: esta es una investigación del tipo cualitativo, llevada a cabo en un municipio de la región metropolitana de João Pessoa, Paraiba, Brasil, considerado prioritario para el control de la enfermedad en el estado de Paraíba. Se utilizó la entrevista semi-estructurada con 8 profesionales de 4 equipos de la Estrategia de Salud de la Familia que estaban acompañando mujeres con tuberculosis en el periodo de recogida de informaciones. Para el análisis del material empírico se utilizó la técnica de análisis de contenido, en su modalidad temática. Resultados: los resultados encontrados realzan el problema de la tuberculosis en el municipio en cuestión, donde los profesionales de salud reconocen la precariedad social en que viven las mujeres con tuberculosis, demuestran poseer una mirada próxima al contexto en que viven esas mujeres, y desarrollan acciones bajo la perspectiva de la integridad y intersectorialidad. Conclusión: la cuestión de género impregna la atención, revelando que los profesionales actúan bajo la perspectiva de la ampliación de la atención. En la interacción con las usuarias se forma un vínculo. No se observan acciones que promuevan empowerment. En vez de ellas se observan actitudes que expresan generosidad. Descriptores: tuberculosis; salud de la familia; salud de la mujer.